Mixed Gastric Carcinomas Show Similar Chromosomal Aberrations in Both their Diffuse and Glandular Components - Beatriz Carvalho; Tineke E. Buffart; Rui M. Reis; Thomas Mons; Cátia Moutinho; Paula Silva; Nicole C. T. van Grieken; Heike Grabsch; Cornelis J. H. van de Velde; Bauke Ylstra; Gerrit A. Meijer; Fátima Carneiro (Cellular Oncology)
Gastric cancer is one of the most frequent malignancies in the world. Nonetheless, the knowledge of the molecular events involved in the development of gastric carcinoma is far from complete. One of the hallmarks of gastric cancer is chromosomal instability resulting in abnormal DNA copy number changes throughout the genome. Mixed gastric carcinomas constitute a rare histological entity, containing the two main histological phenotypes (diffuse and intestinal). Very little is known about the underlying mechanisms of phenotypic divergence in these mixed tumours. To the best of our knowledge only E-Cadherin mutations were implicated so far in the divergence of these tumours and nothing is known about the involvement of chromosome copy number changes in the two divergent histological components. In this study, we compared the DNA copy number changes, in the two different components (diffuse and intestinal) of mixed gastric carcinomas by microarray – comparative genomic hybridisation (array CGH). The analysis of 12 mixed gastric carcinomas showed no significant differences in array CGH profiles between the diffuse and intestinal components of mixed carcinomas. This supports the idea that the phenotypic divergence within mixed gastric carcinomas is not caused by DNA chromosomal aberrations.